2021
DOI: 10.1111/odi.13930
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in cell lines from human ameloblastoma immortalized using hTERT and HPV16‐E6/E7

Abstract: Objective The aim of this study was to evaluate and compare alterations in gene expression using two distinct immortalization methods (hTERT and HPV16‐E6/E7) in ameloblastoma cell lines. Materials and Methods A primary cell culture derived from human ameloblastoma (AME‐1) was established and immortalized by two different methods using a transfection processes to hTERT and HPV‐E6/E7. The RNA‐seq was used to verify which immortalization method had less influence on gene expression. It was performed in four steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…12 In most human cancers telomerase is reactivated during carcinogenesis by expression of the catalytic subunit telomerase reverse transcriptase (TERT), resulting in replicative immortality. 5 Immortalization of ameloblastoma cells through TERT overexpression is a successful model for in vitro research, 13,14 and previous studies showed elevated levels of TERT expression and telomerase activity in ameloblastoma. 10,11,15 Several studies demonstrated that activation of telomerase activity is highly correlated with TERT gene transcription.…”
Section: Resultsmentioning
confidence: 99%
“…12 In most human cancers telomerase is reactivated during carcinogenesis by expression of the catalytic subunit telomerase reverse transcriptase (TERT), resulting in replicative immortality. 5 Immortalization of ameloblastoma cells through TERT overexpression is a successful model for in vitro research, 13,14 and previous studies showed elevated levels of TERT expression and telomerase activity in ameloblastoma. 10,11,15 Several studies demonstrated that activation of telomerase activity is highly correlated with TERT gene transcription.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical data of the AME samples were acquired through medical records with reports present in the files, collected manually, and histologically classified by two oral pathologists. For the in vitro study, the cell line derived from human AME, called AME-hTERT, established at the Cell Culture Laboratory of the Faculty of Dentistry, Federal University of Pará (UFPA) ( Cruz et al, 2021 ), was used. This study was registered and approved by the Human Research Ethics Committee of the Health Sciences Institute of the Federal University of Pará—CEP/ICS/UFPA (CAAE: 30647720.6.0000.0018).…”
Section: Methodsmentioning
confidence: 99%
“…For the in vitro study, the cell line derived from human AME, called AME-hTERT, established at the Cell Culture Laboratory of the Faculty of Dentistry, Universidade Federal do Pará (UFPA), was used [ 32 ]. For the in situ study, 21 cases of conventional AME, ten cases of dentigerous cysts (DC), and ten cases of dental follicles (DF) were collected at the Laboratory of Pathological Anatomy and Immunohistochemistry of the Graduate Program in Dentistry, Universidade Federal do Pará, and Centro Universitário do Pará (CESUPA).…”
Section: Methodsmentioning
confidence: 99%